Perancangan Video Pembelajaran Animasi 2D Mata Pelajaran IPA Proses Fotosintesis di Sekolah Dasar Negeri 04 Sukoharjo - Ririn Rahmawati; Ina Sholihah Widiati (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
As time goes by, technology is developing very rapidly, especially in education, technology can be used to support learning. For example, at SDN 04 Sukoharjo, the author found a problem or obstacle that in science learning, photosynthesis material still uses the lecture method, using LKS books, so it is still monotonous, making students bored and not interested, because photosynthesis material is a biological process that cannot be seen directly. Therefore, researchers utilized technology, especially in multimedia, to create 2D animated learning videos of the photosynthesis process. The research method uses the ADDIE method, namely (Analysis, Design, Development, Implementation, and Evaluation). The final result of this research is a 2D animation learning video of the science lesson process of photosynthesis.